Play Method As Learning Technology In Early Children's Education (PAUD) - Indri Charunnissa (Universitas Terbuka, 2022)
Play is a fun and natural characteristic of every child. Play is also inseparable in early childhood education. When playing, children can learn various skills. Early childhood education prepares students readiness to enter further education. In addition, students need learning activities that support multiple intelligences. This paper discusses a game called Mini Gobak Sodor game. This study uses descriptive-analytic method. This game is an adaptation of traditional Gobak Sodor game with simple and available materials. The content of the game is a religious topic about Islam, including the Five Pillars of Islamic Principles. Children aged 5-6-years old can play this game. The game can be played by four players. The game consists of a drawing divided into six parts. Each part represents pillar of faith in Islamic religion. Each player runs a pawn on the drawing. The study found that the game applied the developmentally appropriate practice (DAP) concept. Therefore in children's education, DAP will allow educators to develop children skills by involving 4 basic components including knowledge, skills, dispositions, and feelings.